Investigation of the potential of Brevibacillus spp. for the biosynthesis of nonribosomally produced bioactive compounds by combination of genome mining with MALDI-TOF mass spectrometry - Jähne, Jennifer; Herfort, Stefanie; Doellinger, Joerg; Lasch, Peter; Tam, Le Thi Thanh; Borriss, Rainer; Vater, Joachim (Frontiers in Microbiology, 2023)
The biosynthetic potential of eleven Brevibacillus spp. strains was investigated by combination of genome mining with mass spectrometric analysis using MALDI-TOF mass spectrometry. These endophytic, plant associated Brevibacillus strains were isolated from crop plants, such as coffee and black pepper, in Vietnam. Draft genomes of these strains were available. They were classified a) by comparison with type strains and a collection of genome-sequenced Brevibacillus spp. deposited in the NCBI data base as well as b) by construction of a phylogenetic tree from the core sequences of publicly available genomes of Brevibacillus strains. They were identified as Brevibacillus brevis (1 strain); parabrevis (2 strains); porteri (3 strains) and 5 novel Brevibacillus genomospecies. Our work was specifically focused on the detection and characterization of nonribosomal peptides produced by these strains. Structural characterization of these compounds was performed by LIFT-MALDI-TOF/TOF mass spectrometric sequence analysis. The highlights of our work were the demonstration of the tyrocidines, a well-known family of cyclodecapeptides of great structural variability, as the main products of all investigated strains and the identification of a novel class of pentapeptides produced by B. brevis; B. schisleri and B. porteri which we designate as brevipentins. Our biosynthetic studies demonstrate that knowledge of their biosynthetic capacity can efficiently assist classification of Brevibacillus species.